Educational potential, underachievement, and cultural pluralism. - Donald Gillies; Sarah Kearns (University of Aberdeen, School of Education, 2016)
This article opens with this striking statement: 'The issue of educational 'underachievement' is one which seems to recur as a crisis every so often in public discourse'. We may consider on re-reading this article how far in this current context of austerity we are once again experiencing a 'crisis narrative' in which we need, like Gillies, to examine and de-construct current dominant notions of 'underachievement' and 'potential'; these notions may encourage educators to pathologise children and families rather than to examine the ways in which the education system may evaluate and miss opportunities to develop children's achievement on the basis of narrow and limiting understandings of their capabilities.